Characteristics and structure of a soy protein isolate–lutein nanocomplex produced via high‐pressure homogenization. (13th April 2022) - Yang, Haodong; Li, Lijia; Xie, Changyuan; He, Mingyu; Guo, Zengwang; Zhao, Shijie; Teng, Fei; Li, Yang
Abstract: BACKGROUND: In recent years, nanocarriers for transporting active substances have attracted attention. This study was to explore the soy protein isolate (SPI) after high‐pressure homogenization (HPH) (0, 30, 60, 90 and 120 MPa) as potential lutein carriers. RESULTS: The load amount (LA) and encapsulation efficiency (EE) of the SPI–lutein nanocomplexes at a homogenization pressure of 60 MPa were the highest (2.32 mg mL −1 and 92.85%, respectively), and the average particle size and ζ‐potential of the SPI–lutein nanocomplexes were 192.1 nm and −30.06 mV, respectively. The DPPH (2, 2‐diphenyl‐1‐picrylhydrazyl) and hydroxyl‐antioxidant activities of the complex increased from 12.4% and 23.3% to 52.7% and 61.07%, respectively, after the protein was treated with HPH. The surface hydrophobicity of the SPI and the SPI–lutein nanocomplexes increased with increasing homogenization pressure treatment. Fourier transform‐infrared spectrophotometry analyses suggested that the homogenization treatments resulted in partial unfolding of the protein molecules, and the addition of lutein can also lead to the change of protein secondary structure. The fluorescence emission of SPI was quenched by lutein through the static quenching mechanism. Fluorescence experiments revealed that SPI and lutein had the strongest binding ability through hydrophobic interaction at a homogenization pressure of 60 MPa. CONCLUSION: After HPH, the combination of SPI and lutein was beneficial, and the stability of lutein also improved after the combination. This study is conducive to expanding the application of soybean protein in the food industry. © 2022 Society of Chemical Industry.